2016
DOI: 10.1177/0731684416684020
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid effect of carbon nanotube film and ultrathin carbon fiber prepreg composites

Abstract: This paper successfully interlaced floating catalyst chemical vapor deposition-grown carbon nanotube film and ultrathin carbon fiber prepreg to achieve strong and flexible carbon nanotube/carbon fiber hybrid composites with high carbon nanotube loading. Epoxidation was also introduced to improve interlaminar interfacial bonding. It was found that pristine carbon nanotube film/carbon fiber interply hybrid composite (carbon fiber/carbon nanotube/carbon fiber) showed sudden and brittle failure, while epoxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…of Synthesis Publications with additional papers from that period added as follows Review papers: 2014 [62,63], 2016 [47], 2017 [64,51]. Post-processing and application papers: 2015 [65,66], 2016 [67,68,69,70,71,72,73,74,75,76,63,77,78,41,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96], 2017 [97,98,99,100,101,102,103,104,105,106,107,108,…”
Section: Parameter Measurement and Characterisationmentioning
confidence: 99%
“…of Synthesis Publications with additional papers from that period added as follows Review papers: 2014 [62,63], 2016 [47], 2017 [64,51]. Post-processing and application papers: 2015 [65,66], 2016 [67,68,69,70,71,72,73,74,75,76,63,77,78,41,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96], 2017 [97,98,99,100,101,102,103,104,105,106,107,108,…”
Section: Parameter Measurement and Characterisationmentioning
confidence: 99%
“…Besides, the fabrication process parameters play a crucial role in determining the flexural properties of the composite 31–35 . In this work, the nozzle temperature of the printer was set as 235°C based on the melting temperature of ABS.…”
Section: Resultsmentioning
confidence: 99%
“…3840 Moreover, previous studies have already revealed that CNTs would form bridging phenomenon at crack tips, which on one hand can passivate and hinder the crack propagation, on the other hand, fracture and pull-out of CNTs form polymer matrix can absorb plenty of energy. 41,42 This reveals that CNTs might be potential in the field of damping materials. Xu et al 43 found that there exists a significant hysteresis phenomenon of the stress–strain behavior when CNTs were pulled out from the polymer matrix.…”
Section: Introductionmentioning
confidence: 88%